The Local and the Global Perspectives on the 20th Century: Günter Grass versus “Time” - Gedutis, Aldis (Problemos, 2004)
The main objective of the article is to compare the global and the local perspectives. We analyze the novel of G. Grass My Century and the collective text 80 days, that changed the world published in an American magazine Time. These texts represent different perspectives – My Century is an example of local perspective, while 80 days, that changed the world pretends to represent the global point of view. Comparative analysis of these texts is grounded upon the fact that both texts discuss and interprets the 20th Century in different ways.